1999
DOI: 10.1046/j.1460-9592.1999.9220329.x
|View full text |Cite
|
Sign up to set email alerts
|

Position of the internal jugular vein in children. A study of the anatomy using ultrasonography

Abstract: The relative anatomy of the internal jugular vein (IJV) was studied in 25 patients undergoing cardiac catheterization under general anaesthesia, with the use of a portable ultrasound probe. In 14 of cases the IJV was anterior, 1 anterolateral and in 10 lateral to the carotid artery between the two heads of the sternocleidomastoid muscle. At the level of the cricoid cartilage, in six cases the IJV was anterior, three anterolateral and in 16 of children the IJV was lateral to the carotid artery. When attempting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
1
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 0 publications
4
34
1
1
Order By: Relevance
“…In the literature, due to technical difficulty, complications are reported with a higher rate for subclavian and jugular vein catheterizations compared to femoral vein catheterization (21)(22)(23). However, in our study, five of six complications which occurred during catheterization were observed during femoral catheterizations, though the difference was not statistically significant.…”
Section: Discussioncontrasting
confidence: 67%
“…In the literature, due to technical difficulty, complications are reported with a higher rate for subclavian and jugular vein catheterizations compared to femoral vein catheterization (21)(22)(23). However, in our study, five of six complications which occurred during catheterization were observed during femoral catheterizations, though the difference was not statistically significant.…”
Section: Discussioncontrasting
confidence: 67%
“…The in-plane puncture technique may require more training, because it implies having the skills to direct the needle exactly within the plane of the probe. Although the evidence base is not yet strong in this regard [20,[45][46][47], this expert panel believes that adequate training for ultrasound-guided central venous access should include knowledge and practice of both techniques.…”
Section: Recommendationsmentioning
confidence: 99%
“…Ultrasound vascular access in neonates and children (Table 3) Clinical experience with ultrasound-guided vascular access in paediatrics started later than in adults [5, 31,32,46,47]. Ultrasound-guided venous access results in a lower technical failure rate (overall and on first attempt), faster access and a reduction in mechanical complications [32,48,49].…”
Section: Integration In Clinical Practicementioning
confidence: 99%
“…It is now well documented that both techniques have serious limitations and are potentially associated with severe complications [99] . In the past ten years, the availability of US guidance for vein cannulation has completely changed the decision-making in venous access in pediatrics [100][101][102][103][104] . Nevertheless, early it was manifest that the use of US lead to an increased rate of successful insertion (both on the whole and at the initial try), quicker cannulation and a reduced rate of insertion-related adverse events [102,105,106] .…”
Section: Neonates Infants Childrenmentioning
confidence: 99%